Metalworkers' nostalgic memories and optimistic official representations of a transformed industrial landscape. Issue 4 (30th May 2016) - Meier, Lars
Abstract: Official representations of transformed landscapes and people's memories of these landscapes are usually set into a contrast. This article analyses the relationship between workers' nostalgic memories and an optimistic official representation of a transformed industrial landscape by considering both as elements of social knowledge. This is achieved by analysing official texts and biographic narratives of workers. All too often class is considered as irrelevant, but this article carves out the relevance of class for workers' memories and their feelings of nostalgia. Against the backdrop of concepts of social knowledge and social memory, this article focuses on the interrelations and demonstrates that official representations leave an imprint on the workers' emotions that are related to class. Correspondingly, this paper clarifies why the retired workers are so nostalgic even if they climbed the social ladder.